Contract Breach and Payment for Environmental Services: A Case from the Kulekhani III Hydroelectric Project in Nepal - Dahal, Khet Raj; Rai, Nabina (Hydro Nepal: Journal of Water, Energy and Environment, 2016)
This study was conducted in 2014. The main objective of this study was to find out the cause of contract breach and Payment for Environmental Services (PES) of Kulekhani III Hydroelectric Project (Kulekhani III HEP). PES is a relatively new concept but it is important as it forces employers, contractors, and local residents of a hydropower project to take a fresh look to support a successful construction effort without causing unnecessary environmental damage. Research findings from responses of local people regarding PES programs, in their respective areas of Kulekhani III Hydroelectric Project have been presented. Hydropower construction is extremely complex works, reliant on a host of individual parties and processes to come together to bring a project to fruition. In every context of Nepal, there are additional challenges in terms of adhering to contractual terms and negotiating governmental and donor agencies requirements for proper construction of hydropower project. In the first half of this paper, it has been explored as a case study in the form of Kulekhani III HEP to provide a record of many overruns the contractor experienced. The project became delayed. There were many causes behind the project delay of Kulekhani III HEP. However, permit for tree clearance for access road and untimely payment for contractors are the major ones. HYDRO Nepal Journal Journal of Water, Energy and Environment Issue: 19 Page: 38-44